Undesirable Aliens in the Diocese of York - Hill, Rosalind M. T. (Studies in church history, 1983)
Placed as they are at the extreme outpost of Western Europe, the British Isles have been, over the centuries of their recorded history and probably for millennia before the Roman invasion, a melting-pot of peoples. R. G. Collingwood described them, correctly if unflatteringly, as an ethnic scrap-heap. As each new set of immigrants arrived they were scrutinised, assessed and usually heavily criticised by the resident population before being allowed to settle down. Matthew Paris may have been a little uncertain as to what, in the thirteenth century, constituted a foreigner, but nevertheless he was quite clear in his own mind that all those whom he considered to be foreigners were bad, unless they stayed in their own countries. Foreign laymen, he suspected, would do anything, even to poisoning their fathers-in-law with blue venom, in order to lay hands on English estates. Foreign clergy were nearly as bad—of one set of Poitevins he remarks that they had faces like play-actors, and were moreover given to wearing indecent boots. Matthew was a particularly intolerant critic, but some two hundred and fifty years later Andrea Trefisano noted that ‘the English have an antipathy to foreigners, and imagine that they never come into the island but to make themselves masters of it, and to usurp English goods,’ although he admits that the natives, when they see a handsome foreigner, are apt to remark that ‘he looks like an Englishman’.